LITERASI MATEMATIS DALAM MENYELESAIKAN MASALAH PERTIDAKSAMAAN LINERA SATU VARIABEL DIKAITKAN DENGAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 6 MELIAU - Klaudia Alina; Mohamad Rifat; Rustam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe mathematical literacy in solving one-variable linear inequality problems in relation to the learning outcomes of class VIII students at SMP Negeri 6 Meliau. The method used in this research is qualitative descriptive research. The research instrument used in this research was test questions. The subjects of this research were class VIII students for the 2023/2024 academic year with a total of 22 students. The type of data collected is the results of students' mathematical literacy tests. Data were analyzed based on mathematical literacy stages and looked at the relationship between mathematical literacy and student learning outcomes. The results of data analysis on students' mathematical literacy abilities at the stage of formulating problems into mathematical form are included in the incapable category, at the stage of using strategies to determine solutions to problems are included in the incapable category, at the stage of interpreting the results obtained are included in the incapable category, the relationship between mathematical literacy with student learning outcomes classified as very strong.